A 12-week intervention with protein-enriched foods and drinks improved protein intake but not physical performance of older patients during the first 6 months after hospital release: a randomised controlled trial. Issue 11 (30th June 2017) - Beelen, Janne; de Roos, Nicole M.; de Groot, Lisette C. P. G. M.
Abstract: During and after hospitalisation, older adults are recommended to consume 1·2–1·5 g of protein/kg body weight per d (g/kg per d) to improve recovery. This randomised controlled trial studied the effectiveness of a 12-week intervention with protein-enriched foods and drinks by following-up seventy-five older patients (mean age: 76·8 (sd 6·9) years) during their first 6 months after hospital discharge. Primary outcomes were protein intake and physical performance (measured with Short Physical Performance Battery (SPPB)). Secondary outcomes for physical recovery were gait speed, chair-rise time, leg-extension strength, hand-grip strength, body weight, nutritional status (Mini Nutritional Assessment), independence in activities of daily living (ADL) and physical activity. The intervention group consumed more protein during the 12-week intervention period compared with the control group ( P <0·01): 112 (sd 34) g/d (1·5 (sd 0·6) g/kg per d) v . 78 (sd 18) g/d (1·0 (sd 0·4) g/kg per d). SPPB total score, gait speed, chair-rise time, body weight and nutritional status improved at week 12 compared with baseline (time effect P <0·05), but were not different between groups. Leg-extension strength, hand-grip strength and independence in ADL did not change. In conclusion, protein-enriched products enabled older adults to increase their protein intake to levels that are higher than their required intake. In these older adults with already adequate protein intakes and limited physical activity, protein enrichment did not enhance physical recovery in the first 6 months after hospital discharge.